Utilisation of Eggshells Powder in Construction of Concrete - Tan, Bing Long; Abdul Rahman, Nurul Syafiqah; Kassim, Suraya; Mokhtar, Mardiha (Multidisciplinary Applied Research and Innovation, 2022)
Many researchers research the potential use of any waste material used in construction material in this era. This statement is due to many countries are going to urbanisation because of population growth. In future, the construction industry will grow since Malaysia is one of the developing countries. During the construction of cement, carbon dioxide gas is released, and it causes environmental pollution and global warming. In order to reduce the impact of carbon dioxide gas in the environment, waste by-products are used as an admixture in this study, so environmental pollution and natural resources consumption can be reduced. Eggshell is generally thrown away as waste, but it contains calcium carbonate. This work has investigated the potential use of eggshell. The egg is one of the waste materials generated from the industry and contributes to the environmental and disposal problem due to the increase of eggshell continuously in recent years. In our research, the laboratory work was carried out into four proportions; 0%, 2%, 5% and 7% of eggshell that has been grind into fine powder. This research aims to investigate the properties of eggshell concrete and gathered from previous researchers and predict the strength of concrete based on laboratory data. A total of 12 cubes were cast, cured and weigh to get the mass as the preliminary data prediction of compressive strength. The analysis is done and forecast using Microsoft Excel using the trendline equation and R2 value from the graph plotted. The prediction result showed eggshell powder in 5% additive in concrete has an excellent compressive strength compared to other proportions, which reduce the concrete’s compressive strength. For recommendation, laboratory work should be conducted for at least seven days of compressive strength for more accurate prediction.